How Right-Wing Extremists Use and Perceive News Media. (September 2019) - Baugut, Philip; Neumann, Katharina
We investigate how right-wing extremists use, perceive, and try to provoke news media coverage. Findings from qualitative interviews with former leaders of right-wing extremist groups in Germany, who served as key informants, show that reports on right-wing extremism are used and trigger feelings of being personally affected. Consequently, right-wing extremists show hostile-media and third-person perceptions. These perceptions influence both emotions and behaviors among right-wing extremists, for example, they cause right-wing leaders to strategically monitor news media to exploit them for political goals. Our findings are presented along with a model and are accompanied by a discussion of the implications for responsible journalism.